Two-stage pattern of Dansgaard–Oeschger 19.2 during MIS 4: Evidence from a high-resolution stalagmite δ18O record in southwestern China and its global correlations - Zhenqiu Zhang; Yifei Wang; Fucai Duan; Jianshun Chen; Dianbing Liu; Qingfeng Shao; Yongjin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Solar forcing of abrupt climate change during early MIS 2: Insights from a 7-year-resolution stalagmite δ18O record in the Asian monsoon region - Pengfei Niu; Fucai Duan; Yifei Wang; Jianshun Chen; Yijia Liang; Qingfeng Shao; Yongjin Wang; Yongqiu Wu (Global and Planetary Change, 2026)

LDHA-Mediated H3K18 Lactylation Promotes the Glycolysis in Non-Small Cell Lung Cancer Through Targeting PTEN - Yufeng Shao; Xiaomin Duan; Guojian Gu; Qingfeng Zhu; Jian Shu; Fan Fei (Biochemical Genetics, 2026)

Review of biological algal fertilizer technology: Alleviating salinization, sequestering carbon, and improving crop productivity - Siyao Dai; Weiying Feng; Fanhao Song; Tingting Li; Yingru Tao; Fang Yang; Qingfeng Miao; Pengcheng Duan; Haiqing Liao; Haibin Shi; José Manuel Gonçalves; Isabel Maria Duarte (Bioresource Technology, 2025)

A new type of triploid fish derived from female Carassius auratus red var. × male Gobiocypris rarus - Fanglei Liu; Ziyi Huang; Xuanyi Zhang; Bei Li; Lujiao Duan; Jianming Yu; Qizhi Liu; Siyang Huang; Hongwen Liu; Qiuli Liang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

The formation and growth characteristics of an all-female hybrid crucian carp - Lujiao Duan; ChaoLiang Shen; Jingjing Lin; Xiaoxia Xiong; Huan Sun; Ziyi Huang; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

Hydroclimate variability over East Asia linked to ocean circulation, Antarctic and Pacific temperature changes during the LGM - Haixin Lu; Fucai Duan; Zhenqiu Zhang; Jianshun Chen; Junji Zhu; Qingfeng Shao; Yongjin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Multi-omics reveals the molecular mechanisms of rapid growth in distant hybrid fish - Xuanyi Zhang; Fanglei Liu; Bei Li; Lujiao Duan; Jianming Yu; Ziyi Huang; SiYang Huang; Hongwen Liu; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

Novel fuel-efficient cryogenic carbon capture system for the combustion exhaust of LNG-powered ships - Qingfeng Jiang; Wenqing Duan; Huaibing Li; Hansheng Feng; Wu Du; Jiayang Gu (International Journal of Refrigeration, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

The key role of myostatin b in somatic growth in fishes derived from distant hybridization - Qingfeng Liu; Lujiao Duan; Bei Li; Xuanyi Zhang; Fanglei Liu; Jianming Yu; Yuqin Shu; Fangzhou Hu; Jingjing Lin; Xiaoxia Xiong; Shaojun Liu (Science China Life Sciences, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Vibrational and stability analysis of internal flow-induced cold-water pipe for OTEC subjected to the clump weight under different boundary conditions - Jian Tan; Chen An; Yu Zhang; Yulong Zhang; Qingfeng Duan; Menglan Duan (Ocean Engineering, 2024)

Stalagmite-based long-term and multi-centennial hydroclimatic variations in southwestern China during the Holocene and relations to global climate change - Fucai Duan; Zhenqiu Zhang; Dianbing Liu; Jianshun Chen; Qingfeng Shao; Yongjin Wang (Quaternary Science Reviews, 2023)

Vibrational Responses of an Ultra-Large Cold-Water Pipe for Ocean Thermal Energy Conversion: A Numerical Approach - Jian Tan; Yulong Zhang; Li Zhang; Qingfeng Duan; Chen An; Menglan Duan (Journal of Marine Science and Engineering, 2023)
The transportation of seawater on a grand scale via an ultra-large cold-water pipe situated within the context of ocean thermal energy conversion (OTEC) floating installations inherently presents challenges associated with instability and potential malfunction in the face of demanding operational circumstances. This study endeavors to augment the stability and security of cold-water pipe (CWP) operations by scrutinizing their vibrational attributes across diverse boundary configurations. Initially, we invoke Euler–Bernoulli beam theory to forge the analytical framework and proffer a semi-analytical resolution by utilizing the generalized integral transform technique (GITT). Subsequently, we authenticate the convergence and precision of our proposed approach through comparative analysis with extant theories. Our findings underscore the conspicuous influence of boundary conditions on the convergence of transverse displacement. The influence of internal flow on the transverse displacement and the natural frequency manifests substantial variability under different boundary conditions. Significantly, an escalation in the internal flow velocity triggers a concomitant reduction in the natural frequency, ultimately culminating in instability once the critical velocity threshold is reached. Additionally, the reliance of the transverse displacement and the natural frequency on the clump weight at the bottom is markedly pronounced. Our discoveries propose that pipe stability can be ameliorated by adjusting the clump weight at the bottom. Furthermore, the novel insights obtained through our proposed approach can significantly aid in the early-stage design and analysis of CWP.

LED-driven sulfamethazine removal and bacterial disinfection by a novel photocatalytic textile impregnated with oxygen vacancy-rich BiO2-x/g-C3N4 hybrid - Jing Wang; Qingfeng Fan; Lidong Kou; Huan Chen; Xing Xing; Wenjie Duan; Kai Jiang (Chemical Engineering Journal, 2023)

Polyaniline@g-C3N4 derived N-rich porous carbon for selective degradation of phenolic pollutants via peroxymonosulfate activation: An electron transfer mechanism - Lidong Kou; Qingfeng Fan; Yuhong Yang; Xianying Duan; Kai Jiang; Jing Wang (Chemosphere, 2023)

Delivery of Helicobacter pylori HpaA to gastrointestinal mucosal immune sites using Lactococcus lactis and its immune efficacy in mice - Rongguang Zhang; Chen Wang; Wenbin Cheng; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan (Biotechnology Letters, 2018)

An engineered Lactococcus lactis strain exerts significant immune responses through efficient expression and delivery of Helicobacter pylori Lpp20 antigen - Rongguang Zhang; Xiaoyan Peng; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Chen Wang; Qingtang Fan; Yuanlin Xi (Biotechnology Letters, 2016)

Construction of a recombinant Lactococcus lactis strain expressing a fusion protein of Omp22 and HpaA from Helicobacter pylori for oral vaccine development - Rongguang Zhang; Guangcai Duan; Qingfeng Shi; Shuaiyin Chen; Qingtang Fan; Nan Sun; Yuanlin Xi (Biotechnology Letters, 2016)